Climate change impacts on the power generation potential of a European mid-century wind farms scenario. (4th March 2016) - Tobin, Isabelle; Jerez, Sonia; Vautard, Robert; Thais, Françoise; van Meijgaard, Erik; Prein, Andreas; Déqué, Michel; Kotlarski, Sven; Maule, Cathrine Fox; Nikulin, Grigory; Noël, Thomas; Teichmann, Claas
Abstract: Wind energy resource is subject to changes in climate. To investigate the impacts of climate change on future European wind power generation potential, we analyze a multi-model ensemble of the most recent EURO-CORDEX regional climate simulations at the 12 km grid resolution. We developed a mid-century wind power plant scenario to focus the impact assessment on relevant locations for future wind power industry. We found that, under two greenhouse gas concentration scenarios, changes in the annual energy yield of the future European wind farms fleet as a whole will remain within ±5% across the 21st century. At country to local scales, wind farm yields will undergo changes up to 15% in magnitude, according to the large majority of models, but smaller than 5% in magnitude for most regions and models. The southern fleets such as the Iberian and Italian fleets are likely to be the most affected. With regard to variability, changes are essentially small or poorly significant from subdaily to interannual time scales.